Rapid Enhancements of the Seed Populations in the Heart of the Earth's Outer Radiation Belt: A Multicase Study. Issue 6 (21st June 2018) - Tang, C. L.; Xie, X. J.; Ni, B.; Su, Z. P.; Reeves, G. D.; Zhang, J.‐C.; Baker, D. N.; Spence, H. E.; Funsten, H. O.; Blake, J. B.; Wygant, J. R.; Dai, G. Y.
Abstract: To better understand rapid enhancements of the seed populations (hundreds of keV electrons) in the heart of the Earth's outer radiation belt ( L*  ~ 3.5–5.0) during different geomagnetic activities, we investigate three enhancement events measured by Van Allen Probes in detail. Observations of the fluxes and the pitch angle distributions of energetic electrons are analyzed to determine rapid enhancements of the seed populations. Our study shows that three specified processes associated with substorm electron injections can lead to rapid enhancements of the seed populations, and the electron energy increases up to 342 keV. In the first process, substorm electron injections accompanied by the transient and intense substorm electric fields can directly lead to rapid enhancements of the seed populations in the heart of the outer radiation belt. In the second process, the substorm injected electrons are first trapped in the outer radiation belt and subsequently transported into L*  < 4.5 by the convection electric field. In the third process, the lower energy electrons are first injected at L*  ~ 5.3 and then undergo drift resonance with ultralow‐frequency waves. These accelerated electrons by ultralow‐frequency waves are further transported into L*  < 4.5 due to the convection electric field. This process is consistent with the radial diffusion. Our results suggest that these specified processes are important for understanding the dynamics of the seed populations in the heart of the outer radiation belt. Key Points: Three specified different processes can lead to rapid enhancements of the seed populations in the heart of the Earth's outer radiation belt The resonant acceleration associated with ULF waves is important for enhancements of the seed populations in L*  ~ 3.5–5.0 These specified processes are important for understanding the dynamics of the seed populations in L*  ~ 3.5–5.0